2003
DOI: 10.1111/j.1525-1438.2003.13376.x
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial carcinoma with recurrence in the incisional scar: A case report

Abstract: We report a case of papillary adenocarcinoma of uterus which developed a recurrence over the scar of surgery. The patient initially underwent surgery followed by adjuvant chemoradiotherapy for her stage II disease. She was disease-free until 21 months when she developed a small mass over the lower site of incisional scar. Fine needle aspiration cytology from this swelling revealed metastatic papillary adenocarcinoma similar to previous histopathology. Treatment of the scar recurrence consisted of palliative ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Fine-needle aspiration diagnosis of metastatic endometrial carcinoma to sites other than bone have been reported,[ 51 52 53 54 55 56 57 58 ] including abdominal wall, breast, pleura, pancreas, tongue, and thyroid. Most of these metastatic tumors were endometrioid carcinomas, with some serous papillary cancers and a few clear cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Fine-needle aspiration diagnosis of metastatic endometrial carcinoma to sites other than bone have been reported,[ 51 52 53 54 55 56 57 58 ] including abdominal wall, breast, pleura, pancreas, tongue, and thyroid. Most of these metastatic tumors were endometrioid carcinomas, with some serous papillary cancers and a few clear cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Probably, the true incidence of the surgical seeding is not well known, but it seems to be an uncommon event, with an overall incidence rate of 5% or less, that rarely results in identifiable metastases. [22][23][24][25][26][27] Concerning skull base tumour sites, Moore et al 23 reported an actuarial risk of incisional relapse of 3% at 1 year in a series of 70 patients treated for sinonasal malignancies with midface and anterior skull base surgery. The possible mechanism of surgical pathway recurrence may be a direct implantation of tumour cells at the time of the surgical procedure or also a haematogenous spread to this particular location in which the increased blood flow and concentration of unknown chemotactic factors may increase the likelihood of tumour cells implantation.…”
Section: Discussionmentioning
confidence: 99%